2012
DOI: 10.1371/journal.pone.0049297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High- versus Low-Intensity Supervised Aerobic and Resistance Training on Modifiable Cardiovascular Risk Factors in Type 2 Diabetes; The Italian Diabetes and Exercise Study (IDES)

Abstract: BackgroundWhile current recommendations on exercise type and volume have strong experimental bases, there is no clear evidence from large-sized studies indicating whether increasing training intensity provides additional benefits to subjects with type 2 diabetes.ObjectiveTo compare the effects of moderate-to-high intensity (HI) versus low-to-moderate intensity (LI) training of equal energy cost, i.e. exercise volume, on modifiable cardiovascular risk factors.DesignPre-specified sub-analysis of the Italian Diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
87
0
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 33 publications
(82 reference statements)
9
87
0
11
Order By: Relevance
“…Based on these data, authors concluded that the HI training is effective in improving the functional capacity and the endothelium-dependent vasodilator response in obese patients with DM2, being an important preventive strategy. Similar result was observed in the Italian Diabetes and Exercise Study, 303 patients (HI and LW intensities groups) improved exercise capacity (VO 2MAX ), insulin sensitivity (HOMA-IR), glycemic control (HbA1C), lipid profile (HDL-c) and strength (1RM), besides reducing systolic and diastolic blood pressure and becoming more physical active after 12 months of treatment [10]. Among the aforementioned variables, the HI and LW groups differed only in muscle strength, HbA1C, and total cholesterol in favor of the HI group.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Based on these data, authors concluded that the HI training is effective in improving the functional capacity and the endothelium-dependent vasodilator response in obese patients with DM2, being an important preventive strategy. Similar result was observed in the Italian Diabetes and Exercise Study, 303 patients (HI and LW intensities groups) improved exercise capacity (VO 2MAX ), insulin sensitivity (HOMA-IR), glycemic control (HbA1C), lipid profile (HDL-c) and strength (1RM), besides reducing systolic and diastolic blood pressure and becoming more physical active after 12 months of treatment [10]. Among the aforementioned variables, the HI and LW groups differed only in muscle strength, HbA1C, and total cholesterol in favor of the HI group.…”
Section: Discussionsupporting
confidence: 84%
“…It is important to highlight the concomitant performance of strength training (60% 1RM) with endurance protocols, which may have influenced the outcome of the research. These studies show that both training intensities are beneficial in DM2 treatment [8,10].…”
Section: Discussionmentioning
confidence: 56%
“…Estos resultados concuerdan con estudios previos donde una intervención con EF de alta intensidad redujo los niveles de IMC y PC en -3,8% y -4,9, respectivamente 17 .…”
Section: Discussionunclassified
“…La magnitud de estos cambios fue de -28% y -26,9% en CT, -24% y -18% en C-LDL, +13% y +10% en C-HDL, -20% y -18% en TG en los grupos HH y NH, respectivamente. Estos cambios son superiores a los reportados en estudios previos por Balducci y col., 17 (-12% glicemia, -11% CT, -20% C-LDL, +6,5% C-HDL y -2,6% TG). No obstante, esta diferencia en los cambios podría estar explicada por las características de los participantes, ya que la intervención de Balducci y col. 17 fue aplicada en personas sin alteraciones metabólicas.…”
Section: Discussionunclassified
See 1 more Smart Citation